2012
DOI: 10.4204/eptcs.102.4
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Microkernel Verification — Specification is the New Bottleneck

Abstract: Software verification tools have become a lot more powerful in recent years. Even verification of large, complex systems is feasible, as demonstrated in the L4.verified and Verisoft XT projects. Still, functional verification of large software systems is rare – for reasons beyond the large scale of verification effort needed due to the size alone. In this paper we report on lessons learned for verification of large software systems based on the experience gained in microkernel verification in the Verisoft XT p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Similar to [3], we observed that strong abstraction capabilities of the used tools are essential. KIV supports arbitrary user-defined data types (given suitable axioms), which was for example exploited to abstract the pointer structure to an algebraic tree and to abstract the sparse pages of files to streams (see Sec.…”
Section: Lessons Learnedsupporting
confidence: 58%
“…Similar to [3], we observed that strong abstraction capabilities of the used tools are essential. KIV supports arbitrary user-defined data types (given suitable axioms), which was for example exploited to abstract the pointer structure to an algebraic tree and to abstract the sparse pages of files to streams (see Sec.…”
Section: Lessons Learnedsupporting
confidence: 58%
“…First, OS kernels (and other system software) contain many interdependent components that are difficult to untangle. Writing down their specifications is already extremely challenging [1]. Making these specifications compositional has a major impact on the overall cost of the entire verification effort.…”
Section: Overviewmentioning
confidence: 99%
“…In this evaluation we did not consider lower levels, including caches and pipelines, as they are not simulated by the underlying emulator. 6 We focused the evaluation on the generally accepted single-error single-bit assumption. This means that for a certain experiment, a fault occurs at any point in time, but only once and is limited to a single register or memory word.…”
Section: B Evaluation Scenario: I4coptermentioning
confidence: 99%
“…Other approaches integrate dependability services into the operating system [10], which simplifies the realization of triple modular redundancy (TMR), but does not protect the kernel itself against transient faults. Even the existing ISO-26262-compliant real-time operating systems ensure only strict isolation of the deployed applications against each other (typically by employing hardware-based memory protection [4] or hypervisor [6] technology), but not against faults that occur in the respective kernel structures.…”
Section: Introductionmentioning
confidence: 99%